Public Debt & Sovereign Ratings - Do Industrialized Countries Enjoy a Privilege? - Bernhard Bartels; Constantin Weiser (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
In this paper, we explore the institutional investors' assessment of relative creditworthiness across selected country groups with a special focus on the impact of public debt on the perception of sovereign risk. Our results show that general government debt is among the most important determinants of credit risk in industrialized countries and emerging markets alike. When using a multivariate framework, we further find that the influence of debt on ratings does not differ between both groups. Also, our results point towards a rating penalty for highly-indebted advanced countries when their debt ratio is associated with a growing one. By contrast, a high debt level alone does not lead to an additional rating decline. Finally, we show that peripheral euro area economies (GIIPS) received a rating privilege before the financial crisis that turned into a penalty after 2008.
Keywords: G24; F34; E62; 330